AUCTION PROBLEMS FOR DEPENDENT RIGHTS BETWEEN THE BANK AS CREDITOR AND DEBTOR - Moertiono, R. Juli (Proceeding International Seminar of Islamic Studies, 2024)
The problem with the norms of Article 8 of Law Number 10 of 1998 mentioned above is that if the debtor defaults, the bank basically can and take the guarantee provided by the creditor as repayment of the debt. But whether the implementation can run that easily, because the debtor himself also has rights that are respected as well, and how the execution process is so that each party, both debtors and creditors in this case the bank is not harmed by its interests, especially regarding guarantees in the form of land encumbered with Dependent Rights. The research method used is qualitative. The results showed that if the debtor defaults, the creditor (bank) basically can and take the guarantee provided by the debtor as repayment of the debt. Right of Liability is a security right for debt repayment, the object of the right of liability is the right to land in accordance with the Basic Agrarian Law, the right of liability can be imposed on the right to land, but it can also be charged along with other objects that are an integral part of the land, with the debtor's default then the creditor reasons to request that the right of liability be auctioned as a step of execution.